Calidad del Diseño de Prueba de admisión 2001-I, Como propuesta en relación a la prueba de Admisión 1999-1, a las diversas carreras de la Universidad nacional de San Martín - Egoavil Rocha, Juanita del Carmen (2001)
The present applied investigation of experimental level was carried out with the students of the Center University Pre of the National University of San Martin - Rioja. The: origin of the: problem, it has been the: evaluation translated in notes desaprobatorias of most of students that surrender admission exams to the Ability of Education and Humanities of the National University of San Martín, vertebrate in the variables desing of Test of Admission 2001-I as proposal and the students of the Center Pre University student. The theoretical sustentation of the proposal Design of Test of Admission 2001-I, it is bounded in function to the theory of the evaluation, to the quality of the evaluation instruments and the selection of the contents of the admission test to the centers of superior education. The alternating central hypothesis, was based on the statement that the proposal Design of Test Admission 2001-I interaccionará significantly determining bigger quantity of students with approbatory notes regarding the Test of Admission 1999-I, this was removed in rum in alternating five operational hypothesis formulated with similar logic in function to the inherent variables to the quality of the evaluation instruments: validity, dependability, objectivity, degree of difficulty and capacity discriminativa. The sample was constituted by four: same groups, two of males and two of women, it was used the simple factorial denominated investigation design and the statistical techniques of variance analysis, percentage calculation, correlation coefficient for spearman ranges, the relationship of index of difficulty and the relationship of capacity discriminativa; the procedure of field work consisted on giving the Test of Admission 2001-I and the Test of Admission 1999-I to the four groups. Made the contrastación of the alternating central hypothesis the results evidenced a critical point of 2, 89. In consequence the conclusions configure 1heir generality specifying the significant interaction of the Design of Test of Admission 2001-1, determining bigger quantity of students of the Center University Pre of the National University of San Martin, headquarters Rioja, with approbatory notes regarding the Test of Admission 1999-I